1978
DOI: 10.1530/jrf.0.0530155
|View full text |Cite
|
Sign up to set email alerts
|

Physical, hormonal and behavioural aspects of sexual development in the marmoset monkey, Callithrix jacchus

Abstract: Measurements of growth, plasma progesterone and testosterone levels, and copulatory behaviour were obtained from captive marmosets from birth until 600-800 days of age. Body weight and knee-to-heel length were similar for both sexes. Males exhibited a neonatal testosterone surge from 15-100 days and testosterone levels began to rise again, coincident with the growth of the testis, at about 250 days. The males were copulating by 400-500 days of age. Paired females were apparently ovulating and able to conceive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
210
3
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(231 citation statements)
references
References 10 publications
17
210
3
1
Order By: Relevance
“…Testicular volumes obtained through ultrasonography were lower than manual measurements (Abbott & Hearn 1978), but were significantly correlated to testicular weight, indicating a linear relationship between them, which has been suggested previously (Jackson & Edmunds 1984). Ultrasonography proved its usefulness in prediction of puberty and testicular development, particularly through gray-scale assessment of testis in this species.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Testicular volumes obtained through ultrasonography were lower than manual measurements (Abbott & Hearn 1978), but were significantly correlated to testicular weight, indicating a linear relationship between them, which has been suggested previously (Jackson & Edmunds 1984). Ultrasonography proved its usefulness in prediction of puberty and testicular development, particularly through gray-scale assessment of testis in this species.…”
Section: Discussionsupporting
confidence: 65%
“…This, in association with available concentrations of testosterone might be the reason why the marmoset initiated copulation between these two age groups (Abbott & Hearn 1978). Our observations about endocrine and reproductive changes around puberty provide substantial baseline values in the marmoset monkey (C. jacchus), which should be helpful in designing future studies in this model.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results showed that androgen levels excreted by adult and juvenile common marmoset males were similar to those found in plasma (27,28), being about 50% lower in juveniles. Adult sons presented significantly higher basal androgen levels than juveniles and also than their fathers but no differences in androgen levels were found between fathers living with adult and juvenile sons.…”
Section: Discussionsupporting
confidence: 80%
“…All females were of adult body size and weight, at least 20 months of age and therefore of reproductive age (common marmoset: Abbott and Hearn, 1978;Goeldi's monkey: Dettling and Pryce, 1999). The study animals were maintained in the primate station of the Anthropological Institute, University of Zurich.…”
Section: Study Animals and Housing Conditionsmentioning
confidence: 99%